Detecting rejection in cardiac transplantation: applications of genomic medicine. (May 2016) - Mohan, Rajeev; Kobashigawa, Jon
The primary focus of care in heart transplant recipients is to prevent rejection. Checking serum levels of immunosuppressant drugs as well as performing biopsies to obtain tissue samples for histological analysis have been the mainstays of rejection surveillance. Novel applications of genomics have proven to be useful in adding a noninvasive alternative to the standard of care. In particular, the use of gene-expression profiling to detect upregulation of rejection-related genes, detection of donor-derived cell-free DNA as a marker of graft apoptosis and rejection, as well as mRNA and miRNA as intragraft and peripheral markers of rejection have come to the forefront of genomics as they relate to transplantation. This review focuses on the use of genomics in heart transplant recipients.